Sequential forward and reverse transport of the Na+ Ca2+ exchanger generates Ca2+ oscillations within mitochondria - Samanta, Krishna; Mirams, Gary R.; Parekh, Anant B. (Nature Publishing Group, 2018)
Mitochondrial Ca2+ homoeostasis regulates aerobic metabolism and cell survival. Ca2+ flux into mitochondria is mediated by the mitochondrial calcium uniporter (MCU) channel whereas Ca2+ export is often through an electrogenic Na+–Ca2+ exchanger. Here, we report remarkable functional versatility in mitochondrial Na+–Ca2+ exchange under conditions where mitochondria are depolarised. Following physiological stimulation of cell-surface receptors, mitochondrial Na+–Ca2+ exchange initially operates in reverse mode, transporting cytosolic Ca2+ into the matrix. As matrix Ca2+ rises, the exchanger reverts to its forward mode state, extruding Ca2+. Transitions between reverse and forward modes generate repetitive oscillations in matrix Ca2+. We further show that reverse mode Na+–Ca2+ activity is regulated by the mitochondrial fusion protein mitofusin 2. Our results demonstrate that reversible switching between transport modes of an ion exchanger molecule generates functionally relevant oscillations in the levels of the universal Ca2+ messenger within an organelle.